Factors Affecting Survival In Patients Undergoing Hemodialysis - MAKHMANOV Lutfullo Saydullayevich; GADAYEV Abdigaffor Gadayevich; GADAYEVA Nilufar Abdigaffarovna (Genius Journals, 2026)
The article examines how age, gender, and several biochemical parameters affect survival to varying degrees in patients undergoing hemodialysis. The results indicate that a number of clinical and demographic factors have a significant negative impact on patient survival. It was found that for every 10-year increase in age, the risk of death rises by 1.61 times, demonstrating a significantly lower survival rate in elderly patients. The 28% higher risk of death in men compared to women is attributed to the higher prevalence of cardiovascular diseases among men. The presence of diabetes mellitus was found to nearly double the risk of death, and in hemodialysis patients, this disease was identified as an independent unfavorable prognostic factor. Chronic heart failure was determined to increase the risk of death by 2.5 times, making it one of the strongest negative factors among those analyzed.
Keywords: hemodialysis; chronic kidney disease; fibroblast-23